An all-inorganic composite high-durability crack repairing material, a preparation method and application thereof

CN123003200APending Publication Date: 2026-10-30CHINA BUILDING MATERIALS ACADEMY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202611360567.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0005]基于以上现有技术的不足,本发明提供了一种全无机复合高耐久裂缝修复材料,旨在解决有机-无机界面不相容、修复机制单一、依赖水存在以及无法覆盖裂缝全生命周期等关键技术问题,实现高效、广谱、自主的多阶段协同裂缝修复

Benefits of technology

1、本发明以结晶型矿物作为唯一自修复功能组分,摒弃了有机微胶囊的使用,由于修复剂与地聚合物基体同属硅铝酸盐-硫酸盐无机体系,从根本上避免了有机-无机界面脱粘、热膨胀系数失配及有机组分在紫外辐照、湿热环境下的老化降解等问题,使修复体系在长期服役过程中保持稳定可靠。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The application discloses a kind of all-inorganic composite high durability crack repair materials and its preparation method and application, including mineral slag powder 50-80 parts, fly ash 15-40 parts, alkali activator 20-40 parts, crystalline mineral self-repairing agent 8-25 parts, nano silicon dioxide 1-5 parts, quartz powder filler 20-50 parts and water 20-40 parts by weight fraction.The present application uses crystalline mineral as the only self-repairing functional component, discards organic microcapsule, eliminates organic-inorganic interface incompatibility and aging degradation problem, realizes the full life cycle coverage of crack from micron level initiation to millimeter level expansion, and self-repairing does not need moisture trigger, can start surface crystallization, suitable for dry environment, and the repair product is chemically homologous with the matrix, there is no weak layer in the interface, which significantly improves the long-term durability and service safety of geopolymer material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of building materials technology, specifically relating to an all-inorganic composite high-durability crack repair material, its preparation method, and its application. Background Technology

[0002] Concrete structures are highly susceptible to cracking during service due to factors such as load, temperature changes, shrinkage deformation, and foundation settlement. Cracks not only affect the structure's appearance and functionality but also provide channels for water and corrosive media to penetrate, leading to decreased concrete durability, accelerated steel corrosion, and serious threats to structural safety and service life. Therefore, self-healing of cracks is a crucial technical approach for achieving long-term durability in concrete structures. Geopolymers, as a novel green cementitious material, have attracted widespread attention in the field of crack repair due to their advantages such as rapid hardening, early strength, resistance to chemical erosion, and good adhesion to concrete substrates. However, geopolymer materials are inherently brittle and prone to developing new microcracks during service; traditional repair materials lack the ability to actively repair newly formed cracks.

[0003] Existing technologies mainly include the following categories: The first category is microcapsule self-healing geopolymer composites. For example, CN121800477A discloses a geopolymer matrix formed by alkaline activation using metakaolin and slag as cementing raw materials, with microcapsules uniformly dispersed, consisting of a polyurethane shell and an epoxy resin core. When cracks occur, the microcapsules rupture to release the epoxy resin, which then fills the cracks after curing, achieving self-healing. CN120229898A discloses a microcapsule for self-healing geopolymer materials, using urea-formaldehyde resin as the wall material and epoxy resin as the core material. At high temperatures of 300-800℃, the shell melts to release the core material, achieving high-temperature crack repair. The second category is intelligent responsive self-healing systems. For example, CN120877935A discloses a sulfuric acid-resistant self-healing geopolymer system. This system uses an in-situ multi-point pH sensing network integrated within the matrix to monitor the evolution of the pH field during erosion in real time. A central AI decision-making module assesses the erosion state and generates the optimal repair strategy to control the self-healing units to perform repairs. The third category is intrinsic self-healing systems, such as the crack self-healing properties of alkali-activated slag powder cementitious materials doped with superabsorbent polymers (SAP), and geopolymer-based penetrating crystalline waterproof materials. These materials utilize the three-dimensional network structure of geopolymer silicon-oxygen tetrahedra, which, combined with active substances, are reactivated and condensed into dense crystals upon contact with water to achieve self-healing.

[0004] However, the aforementioned existing technologies all have significant shortcomings. First, the organic microcapsules such as epoxy resin microcapsules, polyurethane microcapsules, and urea-formaldehyde resin microcapsules used in CN121800477A and CN120229898A exhibit significant interfacial incompatibility with the geopolymer inorganic matrix: firstly, the difference in thermal expansion coefficients between the microcapsule shell and the geopolymer matrix is ​​large, easily leading to interfacial debonding under temperature cycling; secondly, the organic components face aging effects such as ultraviolet radiation and humid heat environments during long-term service, inevitably resulting in molecular chain breakage and performance degradation. Furthermore, the microcapsules in CN120229898A require high temperatures of 300-800℃ to release the core material, severely limiting its application scenarios and failing to meet the self-repair requirements of cracks under normal temperature service conditions. Secondly, the self-repair of pure geopolymer systems mainly relies on the secondary hydration or carbonization reaction of unreacted active components upon contact with water, resulting in low repair efficiency and a passive and uncontrollable repair process; while the incorporation of SAP offers some improvement, SAP itself is an organic polymer material, also facing long-term durability issues. Secondly, existing technologies have a single repair mechanism and lack a multi-stage, time-series coordinated design that covers the entire process of crack initiation from micrometer-level initiation to millimeter-level expansion. Finally, existing self-healing technologies generally rely on the presence of water to activate the repair reaction; the self-healing function cannot be activated in dry environments or without water, severely limiting its application scenarios. Summary of the Invention

[0005] Based on the shortcomings of the existing technologies, this invention provides an all-inorganic composite high-durability crack repair material, aiming to solve key technical problems such as incompatibility of organic-inorganic interfaces, single repair mechanism, dependence on water, and inability to cover the entire life cycle of cracks, so as to achieve efficient, broad-spectrum, autonomous, multi-stage synergistic crack repair.

[0006] The technical solution adopted by the present invention to solve the above-mentioned technical problem is as follows: The present invention discloses an all-inorganic composite high-durability crack repair material, comprising, by weight, 50-80 parts of slag powder, 15-40 parts of fly ash, 20-40 parts of alkali activator, 8-25 parts of crystalline mineral self-healing agent, 1-5 parts of nano-silica, 20-50 parts of quartz powder filler, and 20-40 parts of water.

[0007] Preferably, the slag powder is obtained by grinding granulated blast furnace slag, with a specific surface area of ​​400-600 m² / kg and a 28-day activity index ≥95%.

[0008] Preferably, the fly ash is Class F or Class C fly ash produced by a coal-fired power plant, and the fineness of its residue on a 45µm square hole sieve is ≤20%.

[0009] Preferably, the alkali activator is a composite of water glass and sodium hydroxide with a modulus of 1.0-1.6; the water glass contains 25%-30% SiO2 and 12%-15% Na2O; and the sodium hydroxide is industrial-grade caustic soda flakes with a purity of ≥96%.

[0010] Preferably, the crystalline mineral self-healing agent is a composite of ettringite seed crystals and hydrotalcite-like layered bimetallic hydroxides, wherein the mass ratio of the ettringite seed crystals to the hydrotalcite-like layered bimetallic hydroxides is (2-5):1.

[0011] Preferably, the nano-silica is fumed silica with an average particle size of 10-30 nm, a specific surface area of ​​180-250 m² / g, and a SiO2 content of ≥99.5%.

[0012] Preferably, the quartz powder is made from natural quartzite and has a fineness of 200-325 mesh with continuous gradation and a SiO2 content of ≥98%.

[0013] Another technical problem to be solved by the present invention is to provide a method for preparing the above-mentioned all-inorganic composite high-durability crack repair material, comprising the following steps: S01. Preparation of crystalline mineral self-healing agent: Mix ettringite seed crystals with layered bimetallic hydroxide of hydrotalcite type at a mass ratio of (2-5):1, put them into a planetary ball mill, use zirconia balls as grinding media, make the ball-to-material ratio (5-10):1, rotate at 300-500 r / min, grind for 2-4 hours, until the median particle size D is reached. 50 ≤5µm, discharge for later use, including coarse particles D 50 ≈5µm accounts for 60%-70%, fine particles D 50 Approximately 1µm accounts for 30%-40%; S02. Preparation of powder components: Weigh out slag powder, fly ash, crystalline mineral self-healing agent, nano silica and quartz powder filler according to the ratio, put them into a forced mixer, dry mix them for 10-15 minutes at a speed of 40-60 r / min until the components are macroscopically dispersed and uniform, discharge and seal the package to obtain the powder components. SO3, Preparation of alkaline activator solution: Weigh water glass and sodium hydroxide according to the ratio, add sodium hydroxide to water glass, stir until completely dissolved, adjust the modulus to 1.0-1.6, let stand and cool to room temperature, and then seal and store. S04. Mixing and preparation: Mix the powder components with the alkaline activator solution at a mass ratio of (3-5):1, and add the amount of water specified in the formula. Use an electric stirrer to stir at 400-600r / min for 3-5 minutes until a uniform paste is formed, and the all-inorganic composite high-durability crack repair material is obtained.

[0014] The present invention discloses a method for applying an all-inorganic composite high-durability crack repair material to the repair of cracks in concrete structures, comprising the following steps: Step 1: Base treatment: Chisel a V-shaped or U-shaped groove along the direction of the crack, making the groove 10-30mm wide and 10-25mm deep. Clean the floating dust, oil stains and loose particles in the groove, and clean it with high-pressure air to ensure that the base is firm and clean. Step 2, Interface Treatment: Apply a layer of alkaline activator solution as an interface treatment agent to the cleaned inner surface of the tank, wherein the alkaline activator solution is diluted to 50% of its original concentration; Step 3: Material filling: Use a scraper or caulking gun to embed the well-mixed repair material into the groove, compact it in layers, with each layer not exceeding 10mm in thickness, and ensure that the material is in close contact with the substrate on both sides of the crack. Smooth and finish the surface. Step 4, Maintenance: Cover with plastic film to maintain moisture, keep the temperature not lower than 5℃, and maintain the temperature for at least 72 hours. Keep the surface of the restoration moist during maintenance.

[0015] Compared with the prior art, the advantages of the present invention are: 1. This invention uses crystalline minerals as the sole self-healing functional component, eliminating the use of organic microcapsules. Since the repair agent and the geopolymer matrix both belong to the aluminosilicate-sulfate inorganic system, it fundamentally avoids problems such as debonding at the organic-inorganic interface, mismatch of thermal expansion coefficients, and aging and degradation of organic components under ultraviolet radiation and humid heat environments, thus ensuring that the repair system remains stable and reliable during long-term service.

[0016] 2. This invention constructs a self-healing mechanism that progresses from in-situ crystallization to slow dissolution and then to continuous mineralization, enabling immediate sealing of short-term cracks and dense filling of the middle layer of medium-term cracks, as well as long-term healing of deep cracks. This allows the repair effect to cover the entire process from the micrometer level to the extended millimeter level, significantly improving repair efficiency and repair depth.

[0017] 3. The self-healing agent of this invention exists stably in the geopolymer matrix in the form of crystalline minerals. After cracks are generated, exposure to CO2 in the air can trigger surface-induced crystallization. The repair process can be started without relying on external moisture or secondary hydration reaction of the matrix. It still has self-healing ability under dry or anhydrous conditions, which greatly expands the applicability of self-healing geopolymer materials in arid areas, underground engineering and indoor dry environments. Detailed Implementation

[0018] The technical solution of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0019] This invention discloses an all-inorganic composite high-durability crack repair material, comprising, by weight, 50-80 parts of slag powder, 15-40 parts of fly ash, 20-40 parts of alkali activator, 8-25 parts of crystalline mineral self-healing agent, 1-5 parts of nano-silica, 20-50 parts of quartz powder filler, and 20-40 parts of water, wherein: (1) Raw materials The slag powder is a fine powder obtained by grinding granulated blast furnace slag. It has a specific surface area of ​​400-600 m² / kg and a 28-day activity index ≥95%. Its main chemical components, by weight percentage, are CaO 35%-45%, SiO₂ 30%-40%, and Al₂O₃ 15%-30%. The slag powder provides the main silica-alumina components and calcium source in the geopolymer system, and under alkali activation, it generates CASH geopolymer gel.

[0020] Fly ash refers to Class F or Class C fly ash produced by coal-fired power plants, with a fineness of ≤20% residue on a 45µm square-hole sieve. Its main chemical components are SiO2 and Al2O3. The incorporation of fly ash can supplement the aluminum component of the system, regulate the Si / Al ratio of the geopolymer gel, and improve the workability and later strength of the material.

[0021] The alkali activator is a composite of water glass and sodium hydroxide with a modulus of 1.0-1.6; the water glass contains 25%-30% SiO2 and 12%-15% Na2O; the sodium hydroxide is industrial-grade caustic soda flakes with a purity ≥96%. The alkali activator provides a highly alkaline environment (pH ≥13), which promotes the dissolution, depolymerization, and condensation of silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra in slag powder and fly ash to form a three-dimensional geopolymer network.

[0022] Crystalline mineral self-healing agents consist of ettringite (3CaO·Al2O3·3CaSO4·32H2O) seed crystals and layered double hydroxides (LDHs, general formula [M]). 2+ 1-x M 3+ x (OH)2] x+ (A n- ) x / n ·mH2O, where M 2+ Mg 2+ Ca 2+M 3+ For Al 3+ Fe 3+ A n- CO3 2- SO4 2- The complex consists of ettringite seed crystals and layered bimetallic hydroxides of the same type, with a mass ratio of (2-5):1. The ettringite seed crystals exposed on the crack surface act as nucleation sites, adsorbing CO2 and moisture from the air, inducing heterogeneous nucleation and crystallization of calcium carbonate on the seed crystal surface, thus achieving rapid sealing of the crack surface. The ettringite slowly dissolves in the pore fluid, releasing Ca2+. 2+ Al 3+ and SO4 2- Ions react with silicate ions in the matrix to form secondary ettringite and CSH gel; the crystal growth of ettringite is accompanied by a significant increase in solid volume, which can compensate for the chemical shrinkage and drying shrinkage of the geopolymer matrix. Interlayer CO3 in hydrotalcite-based LDHs 2- or SO4 2- It can react with corrosive anions (Cl) that seep into the cracks. - SO4 2- (etc.) exchange occurs, capturing harmful ions; LDHs slowly dissolve in an alkaline environment, releasing Mg 2+ Al 3+ Plasma induces layered bimetallic hydroxide mineralization and deposition deep within the cracks; its layered structure can adsorb OH⁻ ions, acting as a pH buffer in the microenvironment, which is conducive to the stable formation of remediation products.

[0023] The nano-silica is fumed silica with an average particle size of 10-30 nm, a specific surface area of ​​180-250 m² / g, and a SiO₂ content of ≥99.5%. The nano-silica fills the nanoscale pores in the polymer gel, improving the matrix density and mechanical properties.

[0024] Quartz powder is made from natural quartzite, with a fineness of 200-325 mesh continuous gradation and a SiO2 content of ≥98%. Its main functions are to adjust the consistency of materials and control costs.

[0025] (2) Preparation method, including the following steps: S01. Preparation of crystalline mineral self-healing agent: Mix ettringite seed crystals with hydrotalcite-based LDHs at a mass ratio of (2-5):1, and put them into a planetary ball mill. Use zirconia balls as the grinding medium, making the ball-to-material ratio (5-10):1, and grind at a speed of 300-500 r / min for 2-4 hours until the median particle size D is reached. 50 ≤5µm, discharge for later use, including coarse particles D 50 ≈5µm accounts for 60%-70%, fine particles D 50Approximately 1µm accounts for 30%-40%; S02. Preparation of powder components: Weigh out slag powder, fly ash, crystalline mineral self-healing agent, nano silica and quartz powder filler according to the ratio, put them into a forced mixer, dry mix them for 10-15 minutes at a speed of 40-60 r / min until the components are macroscopically dispersed and uniform, discharge and seal the package to obtain the powder components. SO3, Preparation of alkaline activator solution: Weigh water glass and sodium hydroxide according to the ratio, add sodium hydroxide to water glass, stir until completely dissolved, adjust the modulus to 1.0-1.6, let stand and cool to room temperature, and then seal and store. S04. Mixing and preparation: Mix the powder components with the alkaline activator solution at a mass ratio of (3-5):1, and add the amount of water specified in the formula. Use an electric stirrer to stir at 400-600r / min for 3-5 minutes until a uniform paste is formed, and the all-inorganic composite high-durability crack repair material is obtained.

[0026] (3) The application method in the repair of cracks in concrete structures includes the following steps: Step 1: Base treatment: Chisel a V-shaped or U-shaped groove along the direction of the crack, making the groove 10-30mm wide and 10-25mm deep. Clean the floating dust, oil stains and loose particles in the groove, and clean it with high-pressure air to ensure that the base is firm and clean. Step 2, Interface Treatment: Apply a layer of alkaline activator solution as an interface treatment agent to the cleaned inner surface of the tank, wherein the alkaline activator solution is diluted to 50% of its original concentration; Step 3: Material filling: Use a scraper or caulking gun to embed the well-mixed repair material into the groove, compact it in layers, with each layer not exceeding 10mm in thickness, and ensure that the material is in close contact with the substrate on both sides of the crack. Smooth and finish the surface. Step 4, Maintenance: Cover with plastic film to maintain moisture, keep the temperature not lower than 5℃, and maintain the temperature for at least 72 hours, keeping the surface of the restoration moist during this period.

[0027] The specifications of the raw materials used in the following examples and comparative examples are as follows: the specific surface area of ​​the slag powder is 450 m². 2 / kg, 28d activity index is 98%; fly ash is Class F, 45µm sieve residue ≤15%; in the alkali activator, water glass and NaOH are used together to adjust the modulus, wherein Example 1 is modulus 1.4 and Example 2 is modulus 1.2; in the crystalline mineral self-healing agent, the ettringite seed crystal:LDHs=3:1 in Example 1 and the ettringite seed crystal:LDHs=4:1 in Example 2, D 50The particle size was ≤5µm. Comparative Example 1 did not include a crystalline mineral self-healing agent; Comparative Example 2 contained only a single ettringite seed crystal; and Comparative Example 3 replaced the crystalline mineral self-healing agent with an equal amount of epoxy resin microcapsules. The preparation of these epoxy resin microcapsules was based on patent CN121800477A. ​​The average particle size of the nano-silica was 15nm, and the specific surface area was 220m². 2 / g; the quartz powder filler is 280 mesh continuously graded; the water is tap water.

[0028] Preparation of crystalline mineral self-healing agent: Eettsonite seed crystals and hydrotalcite-based LDHs (Mg-Al-CO3 type) were mixed at a mass ratio of 3:1 and fed into a planetary ball mill. Zirconia balls were used as the grinding media, with a ball-to-material ratio of 8:1, a rotation speed of 400 r / min, and grinding for 3 hours until the median particle size D was reached. 50 ≈4.5μm, of which coarse particles D 50 ≈5μm accounts for 65%, fine particles D 50 Approximately 1μm, accounting for 35%, is discharged for later use.

[0029] Table 1 lists the components and their weight parts for Examples 1-2 and Comparative Examples 1-3.

[0030]

[0031] Examples 1-2 and Comparative Examples 1-3 were prepared according to the following steps: (1) Preparation of powder components: Weigh out slag powder, fly ash, crystalline mineral self-healing agent (replaced by epoxy resin microcapsules in Comparative Example 3), nano silica and quartz powder filler according to the ratio, put them into a forced mixer, dry mix for 12 minutes at a speed of 50 r / min, and then discharge and seal the package.

[0032] (2) Preparation of alkaline activator solution: Weigh water glass and sodium hydroxide according to the ratio, add sodium hydroxide to water glass, stir until completely dissolved, adjust the modulus, let stand and cool to room temperature, and then seal and store.

[0033] (3) On-site construction mixing: Mix the powder components with the alkali activator solution at a mass ratio of 4:1, and add the amount of water specified in the formula. Use an electric mixer to stir for 4 minutes at 500r / min until a uniform paste is formed.

[0034] (4) Construction and curing: Fill the precast concrete cracks (the base layer has been treated) according to the above application method, cover with plastic film for moisture retention and curing, temperature 23±2℃, and test the performance after curing to the specified age.

[0035] The repair materials prepared in Examples 1-2 and Comparative Examples 1-3 were subjected to performance tests. The technical indicators are shown in Table 2, and the performance test results are shown in Table 3.

[0036] Table 2 lists the technical specifications for each performance test.

[0037]

[0038] Table 3 lists the performance test results of Examples 1-2 and Comparative Examples 1-3.

[0039]

[0040] As shown in Tables 1 and 3, the performance indicators of Examples 1 and 2 are significantly better than those of the comparative example. The repair rate is ≥68% after 7 days, ≥88% after 28 days, and ≥93% after 90 days. Under dry conditions, the repair rate is ≥55% after 7 days, the maximum repairable crack width is ≥0.60 mm, and the repair rate retention rate after aging is ≥90%, confirming its high innovation and practicality as a fully inorganic self-healing crack repair material. Comparing Example 1 with Comparative Example 1, it is evident that without the crystalline mineral self-healing agent, the self-healing ability of the pure geopolymer system in Comparative Example 1 is extremely limited, mainly relying on the accidental secondary hydration of unreacted components. However, after incorporating the crystalline mineral self-healing agent, the repair rate in Example 1 increased by approximately 3.8 times after 7 days, approximately 2.8 times after 28 days, and approximately 2.5 times after 90 days. This proves that the crystalline mineral self-healing agent is the core functional component for achieving efficient and continuous self-healing. Comparing Example 1 with Comparative Example 2, it is evident that the single ettringite seed system in Comparative Example 2 has a better repair effect in the early stages, but... The improvement in repair rate in the later stages is limited, and it lacks deep and continuous repair capabilities. In contrast, the ettringite seed + LDHs composite system of Example 1 not only has a better early repair effect, but also continues to improve to 94% in the later stages. This proves that LDHs are a key technical feature to ensure long-term self-healing effects. As can be seen from the comparison between Example 1 and Comparative Example 3, the organic microcapsule system of Comparative Example 3 has a certain self-healing effect in the short term, but the repair rate is extremely low in dry environments. This is because the curing of epoxy resin depends on crack propagation triggering, and it cannot be effectively released when dry and the crack has not further propagated. Secondly, the repair ability is severely reduced after aging, and the organic components face the problems of ultraviolet aging and thermo-oxidative aging. Thirdly, the maximum repairable crack width is limited. In contrast, the all-inorganic system of Example 1 of this invention still maintains a 55% repair rate in dry environments, and the repair rate retention rate after aging is as high as 92%, with a maximum repairable crack width of 0.65 mm. This proves that the all-inorganic self-healing route is superior to the organic microcapsule route in terms of environmental adaptability, durability and repair ability.

[0041] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A fully inorganic composite high-durability crack repair material, characterized in that: The ingredients, by weight, include 50-80 parts slag powder, 15-40 parts fly ash, 20-40 parts alkali activator, 8-25 parts crystalline mineral self-healing agent, 1-5 parts nano silica, 20-50 parts quartz powder filler, and 20-40 parts water.

2. The all-inorganic composite high-durability crack repair material according to claim 1, characterized in that: The slag powder is obtained by grinding granulated blast furnace slag, with a specific surface area of ​​400-600 m² / kg and an activity index of ≥95% after 28 days.

3. The all-inorganic composite high-durability crack repair material according to claim 1, characterized in that: The fly ash is Class F or Class C fly ash produced by coal-fired power plants, and the fineness of its residue on a 45µm square hole sieve is ≤20%.

4. The all-inorganic composite high-durability crack repair material according to claim 1, characterized in that: The alkali activator is a composite of water glass and sodium hydroxide with a modulus of 1.0-1.6; the water glass contains 25%-30% SiO2 and 12%-15% Na2O; the sodium hydroxide is industrial-grade caustic soda flakes with a purity ≥96%.

5. The all-inorganic composite high-durability crack repair material according to claim 1, characterized in that: The crystalline mineral self-healing agent is a composite of ettringite seed crystals and hydrotalcite-like layered bimetallic hydroxides, with a mass ratio of ettringite seed crystals to hydrotalcite-like layered bimetallic hydroxides of (2-5):

1.

6. The all-inorganic composite high-durability crack repair material according to claim 1, characterized in that: The nano-silica is fumed silica with an average particle size of 10-30 nm, a specific surface area of ​​180-250 m² / g, and a SiO2 content of ≥99.5%.

7. The all-inorganic composite high-durability crack repair material according to claim 1, characterized in that: The quartz powder is made from natural quartzite and has a fineness of 200-325 mesh with continuous gradation and a SiO2 content of ≥98%.

8. A method for preparing an all-inorganic composite high-durability crack repair material according to any one of claims 1-7, characterized in that... Includes the following steps: S01. Preparation of crystalline mineral self-healing agent: Mix ettringite seed crystals with layered bimetallic hydroxide of hydrotalcite type at a mass ratio of (2-5):1, and put them into a planetary ball mill. Use zirconia balls as the grinding medium to make the ball-to-material ratio (5-10):1, and the rotation speed is 300-500 r / min. Grind for 2-4 hours until the median particle size D is reached. 50 ≤5µm, discharge for later use, including coarse particles D 50 ≈5µm accounts for 60%-70%, fine particles D 50 Approximately 1µm accounts for 30%-40%; S02. Preparation of powder components: Weigh out slag powder, fly ash, crystalline mineral self-healing agent, nano silica and quartz powder filler according to the ratio, put them into a forced mixer, dry mix them for 10-15 minutes at a speed of 40-60 r / min until the components are macroscopically dispersed and uniform, discharge and seal the package to obtain the powder components. S03. Preparation of alkaline activator solution: Weigh water glass and sodium hydroxide according to the ratio, add sodium hydroxide to water glass, stir until completely dissolved, adjust the modulus to 1.0-1.6, let stand and cool to room temperature, then seal and store to obtain alkaline activator solution; S04. Mixing and preparation: Mix the powder components with the alkaline activator solution at a mass ratio of (3-5):1, and add the amount of water specified in the formula. Use an electric stirrer to stir at 400-600r / min for 3-5 minutes until a uniform paste is formed, and the all-inorganic composite high-durability crack repair material is obtained.

9. The application method of the all-inorganic composite high-durability crack repair material according to any one of claims 1-7 in the repair of cracks in concrete structures, comprising the following steps: Step 1: Base treatment: Chisel a V-shaped or U-shaped groove along the direction of the crack, making the groove 10-30mm wide and 10-25mm deep. Clean the floating dust, oil stains and loose particles in the groove, and clean it with high-pressure air to ensure that the base is firm and clean. Step 2, Interface Treatment: Apply a layer of alkaline activator solution as an interface treatment agent to the cleaned inner surface of the tank, wherein the alkaline activator solution is diluted to 50% of its original concentration; Step 3: Material filling: Use a scraper or caulking gun to embed the well-mixed repair material into the groove, compact it in layers, with each layer not exceeding 10mm in thickness, and ensure that the material is in close contact with the substrate on both sides of the crack. Smooth and finish the surface. Step 4, Curing: Cover with plastic film to maintain moisture, keep the curing temperature not lower than 5℃, and keep the curing time not less than 72 hours. Keep the surface of the restoration moist during curing.

Citation Information

Patent Citations

  • Microcapsule for self-repairing geopolymer material, and preparation method and application thereof

    CN120229898A

  • Sulfuric acid erosion resistant self-repairing geopolymer system and self-repairing method thereof

    CN120877935A

  • Microcapsule self-repairing geopolymer composite material and preparation method thereof

    CN121800477A